Environmentally Friendly and Recyclable CuCl2-Mediated C–S Bond Coupling Strategy Using DMEDA as Ligand, Base, and Solvent - Shen, Guodong; Lu, Qichao; Wang, Zeyou; Sun, Weiwei; Zhang, Yalin; Huang, Xianqiang; Sun, Manman; Wang, Zhiming (Synthesis, 2021)
Simple reaction conditions and recyclable reagents are crucial for environmentally friendly industrial applications. An environment-friendly, recyclable and economic strategy was developed to synthesize diaryl chalcogenides by the CuCl2-catalyzed C–S bond-formation reaction via iodobenzenes and benzenethiols/1,2-diphenyldisulfanes using N,N′-dimethylethane-1,2-diamine (DMEDA) as ligand, base, and solvent. For these reactions, especially the reactions of diiodobenzenes and aminobenzenethiols/disulfanediyldianilines, a range of substrates are compatible and give the corresponding products in good to excellent yields. Both of the reagents in the catalytic system (CuCl2/DMEDA) are inexpensive, conveniently separable, and recyclable for more than five cycles.
Keywords: environment friendly; recyclable; C–S bond coupling; DMEDA; CuCl2